탄소 나노튜브 함유 Solderable 이방성 도전성 접착제의 신뢰성 특성에 관한 연구 - 임병승(Byung-Seung Yim); 이정일(Jeong Il Lee); 김종민(Jong-Min Kim) (Journal of welding and joining, 2017)
In this paper, two types of assemblies using CNT-filled SACAs (with 0.03 wt% CNTs and without CNT) were prepared to investigate the influence of carbon nanotubes (CNTs) on the reliability properties of solderable anisotropic conductive adhesives (SACAs) with a low-melting-point alloy (LMPA). Two types of reliability test including thermal shock (TS: -55 to $125^{°}C$, 1000 cycles) and high-temperature and high-humidity (HTHH: $85^{°}C$, 85% RH, 1000 h) tests were conducted. The SACA assemblies with and without CNTs showed stable electrical reliability properties due to the formation of wide and stable metallurgical interconnection between corresponding metallizations by the molten LMPA fillers. Although the mechanical pull strength of CNT-filled SACA assemblies was decreased after thermal aging (because of the excessive layer growth and planarization of the IMCs), the CNT-filled SACA with 0.03wt% CNTs showed enhanced mechanical reliability properties compared with the SACA assemblies no CNTs. This enhancement in mechanical performance was due to the reinforcement effect of the CNTs. These results demonstrate that CNTs within the CNT-filled SACAs can improve the reliability properties of CNT-filled SACAs joints due to their superior physical properties.